Development and validation of a novel risk model for predicting atrial fibrillation recurrence risk among paroxysmal atrial fibrillation patients after the first catheter ablation - Li, Guangling; Wang, Xiaomei; Han, Jing-jing; Guo, Xueya (Frontiers in Cardiovascular Medicine, 2022)
Aims: Several models have been developed to predict the risk of atrial fibrillation (AF) recurrence after radiofrequency catheter ablation (RFCA). However, these models are of poor quality from the start. We, therefore, aimed to develop and validate a predictive model for postoperative recurrence of AF. Methods: In a study including 433 patients undergoing the first circumferential pulmonary vein isolation (CPVI) procedure, independent predictors of AF recurrence were retrospectively identified. Using the Cox regression of designated variables, a risk model was developed in a random sample of 70% of the patients (development cohort) and validated in the remaining (validation cohort) 30%. The accuracy and discriminative power of the predictive models were evaluated in both cohorts. Results: During the established 12-months follow-up, 134 patients (31%) recurred. Six variables were identified in the model including age, coronary artery disease, heart failure, hypertension, transient ischemic attack or cerebrovascular accident, and left atrial diameter. The model showed good discriminative power in the development cohort, with an AUC of 0.77 (95% CI, 0.69-0.86). Furthermore, the model shows good agreement between actual and predicted probabilities in the calibration curve. The above results were confirmed in the validation cohort. Meanwhile, decision curve analysis for this model also demonstrates the advantages of clinical application. Conclusion: A simple risk model to predict AF recurrence after ablation was developed and validated, showing good discriminative power and calibration.